Influencing Factors in Selecting STREAM for Better Future among the Pre-University Students - Julinamary Parnabas; Sri Manasa Raja Sekar; Muhammad Raziq Adnan Rizal Adnan; Subhasree Suresh; Neithyashankari Parkesh; Tanishvini Raja (Kolej PERMATA Insan, 2024)
"STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan